1998
DOI: 10.2307/1251740
|View full text |Cite
|
Sign up to set email alerts
|

The Convergence of Planning and Execution: Improvisation in New Product Development

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. American Marketing Association is collaborating with JSTOR to digitize, preserve and extend access to Journal of Marketing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
513
1
24

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 422 publications
(550 citation statements)
references
References 18 publications
12
513
1
24
Order By: Relevance
“…Conceptual framework on the critical drivers of project learning and time-to-market necessary to handle the increasing amount of information. Innovative communication is necessary during the service innovation process, as successful innovations need experimentation and improvisation (Moorman and Miner, 1998;Eisenhardt and Tabrizi, 1995). The innovation process contains a lot of uncertainty that the firm has to manage by supporting creativity and the exchange of ideas.…”
Section: Discussionmentioning
confidence: 99%
“…Conceptual framework on the critical drivers of project learning and time-to-market necessary to handle the increasing amount of information. Innovative communication is necessary during the service innovation process, as successful innovations need experimentation and improvisation (Moorman and Miner, 1998;Eisenhardt and Tabrizi, 1995). The innovation process contains a lot of uncertainty that the firm has to manage by supporting creativity and the exchange of ideas.…”
Section: Discussionmentioning
confidence: 99%
“…Improvisation is 'action as it unfolds' (Moorman & Miner, 1998a) or, if you prefer to articulate this in more project-based terms, planning simultaneous with execution.…”
Section: Pm Trendsmentioning
confidence: 99%
“…We reviewed literature that is concerned with planning activities in NPD (e.g., Thieme, et al, 2003;MacCormack and Verganti, 2003;Miner, et al, 2001;Song and Montoya-Weiss, 1998;Moorman and Miner, 1998) and drew on propositions from our previous research findings (Herstatt, et al, 2004a;Herstatt, et al, 2004b) to develop a standardized questionnaire.…”
Section: Methodsologymentioning
confidence: 99%
“…Research has shown that advanced planning in NPD projects positively contributes to a number of success measures, such as time, reduction of failure rates, financial returns and innovation levels (Moorman and Miner, 1998). However, traditional planning efforts have also been criticized for exerting too much formalism and control, and thereby hindering creativity (Bart, 1993).…”
Section: Aim Of the Studymentioning
confidence: 99%
See 1 more Smart Citation